Ngn2-Induced Differentiation of the NG108-15 Cell Line Enhances Motor Neuronal Differentiation and Neuromuscular Junction Formation - Madeline Meli; Kristy Swiderski; Jinchao Gu; Ben Rollo; Ben Bartlett; Marissa K. Caldow; Gordon S. Lynch; Patrick Kwan; Huseyin Sumer; Brett Cromer (Biomolecules)
The neuronal progenitor NG108-15 neuroblastoma x glioma cell line proliferates indefinitely in vitro and is capable of directed differentiation into cholinergic neurons. The cell line is a robust model for investigating neuronal differentiation and function in vitro. The lineage-specific transcription factor-mediated differentiation of pluripotent stem cell lines (PSCs) leads to more rapid, efficient, and functional neurons. In this study, we tested the hypothesis that transcription factors could also drive the fate of an immortalised cell line. We first established a stable NG108-15 cell line, by piggyBac (pBac) transposition, that conditionally expresses neurogenin-2 (Ngn2), a common transcription factor for specifying neuronal fate. Following doxycycline-induction of Ngn2, we observed more rapid and efficient differentiation, and improved neurite outgrowth and viability compared with the WT cell line. Moreover, when co-cultured with C2C12 mouse myotubes, the modified NG108-15 cells resulted in significantly larger acetylcholine receptor (AChR) aggregates, suggesting enhanced neuromuscular junction (NMJ) formation. These findings describe a novel methodology for differentiating NG108-15 cells more efficiently, to enhance the usefulness of the cell line as a motor neuron model.